2014
DOI: 10.4172/2155-9546.1000269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bamboo Charcoal Added Feed on Reduction of Ammonia and Growth of Pangasius hypophthalmus

Abstract: A 50-day feeding trial was conducted to determine the effects of dietary bamboo charcoal (BC) on ammonia (NH 3 -N) excretion and growth performances of Pangasius hypophthalmus. Four levels of BC (0%, 0.5%, 1% and 2%) were supplemented to the diet composition and fed to fish (initial body weight 1.18 ± 0.04 g) twice a day. At the end of the trial, mean of final weight (g), final length (cm), weight gain (g), length gain (cm), percent weight gain, percent length gain, specific growth rate (% per day), feed conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Previous studies on the effects of dietary charcoal supplementation in animals have largely focused on mammals and some fish species, with a particular focus on animal growth [22][23][24][25]. However, to the best of our knowledge, the effects of dietary charcoal supplementation on trace element uptake and antioxidant performance in fish have not been previously characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the effects of dietary charcoal supplementation in animals have largely focused on mammals and some fish species, with a particular focus on animal growth [22][23][24][25]. However, to the best of our knowledge, the effects of dietary charcoal supplementation on trace element uptake and antioxidant performance in fish have not been previously characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, AC and WC-supplemented diets positively decreased ammonia levels, with no significant differences between the higher levels (WC-2 and AC-2) and lower levels (WC-1, AC-1). This differs slightly from the conclusion that greater dietary charcoal in fish feed causes a decrease in TAN excretion [21,24,52]. The differences between the recommended levels of WC and AC may be attributable to variances in culture practices, water quality standards, fish species, and the quality of dietary protein sources.…”
Section: Discussionmentioning
confidence: 58%
“…Lan et al (2016) found that growth rates revealed that using 1% rice husk-based biochar to feed striped catfish (Pangasius hypophthalmus) were increased by 36% (p < .05). Quaiyum, Jahan, Jahan, Akhter, and Sadiqul (2014) observed that 2% of bamboo biochar added to the daily diet of striped catfish significantly increased their body weight, survival rate, FCR and SGR. .…”
Section: Fishmentioning
confidence: 87%